Perspectives on Arabic linguistics XXVI : papers from the annual symposium on Arabic linguistics, New York, 2012 - Khamis-Dakwar, Reem; Froud, Karen (Studies in Arabic linguistics, 2014)
Diglossia is one distinctive feature of Arabic and other languages, such as Swiss-German (Ferguson 1959). Neurocognitive studies aiming to understand the neural mechanisms of diglossia in general, and Arabic diglossia in particular, are sparse. This paper provides a framework for discussing neurophysiological approaches to questions concerning the representation and processing of languages exhibiting diglossia in the brains of native speakers, as well as understanding the potential contribution of such approaches for applied linguistics and teaching Arabic as a first or second language.